Modern slavery and supply chain transparency - New, S (Oxford University Press, 2020)
The scourge of modern slavery has led to legislation in various countries requiring firms to engage in a particular form of supply chain transparency. However, these regulatory initiatives have been widely perceived to be, by themselves, a weak response to such a serious challenge. This chapter argues that assessment of these initiatives hinges on the interpretation of modern slavery itself: Are extreme forms of labor exploitation aberrations of an otherwise blameless system, or are they intrinsic to the functioning of contemporary global capitalism? If the latter, then new types of transparency might be needed that go beyond firms reporting on their policies and efforts. The chapter introduces the idea of interrogational transparency as a mechanism by which civil society actors (including consumers, activists, and researchers) can develop accountability dialogues with powerful corporations. To illustrate these points, the chapter examines emergent patterns of transparency within the food giant Nestlé.